The Romance of Interpretation Visionary Criticism from Pater to De Man - O’Hara, Daniel T. (Columbia University Press, 1985)
Studies five major critical theorists, Pater, Bloom, Hartman, Frye, and de Man, of the Romantic imagination
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Apr 2019)
Keywords: LITERARY CRITICISM / Modern / 19th Century